Isolation of an indigenous Chlorella vulgaris from swine wastewater and characterization of its nutrient removal ability in undiluted sewage. (November 2017) - Wen, Yangmin; He, Yongjin; Ji, Xiaowei; Li, Shaofeng; Chen, Ling; Zhou, Youcai; Wang, Mingzi; Chen, Bilian
Graphical abstract: Highlights: An indigenous microalgal strain was isolated and identified as Chlorella vulgaris . The isolated microalgae could grow well in undiluted swine slurry. TN and TP removal ratios of isolated microalgae were over 90% in swine slurry. The level of 5-mC was inversely proportional to the growth of isolated microalgae. Abstract: Bio-treatment of wastewater mediated by microalgae is considered as a promising solution. This work aimed to isolate an indigenous microalgal strain (named MBFJNU-1) from swine wastewater effluent and identify as Chlorella vulgaris . After 12 days, the removal efficiencies of total nitrogen (TN) and total phosphorus (TP) in undiluted swine slurry were 90.51% and 91.54%, respectively. Stress tolerance in response to wastewater was verified by cultivating in artificial wastewater containing different levels of chemical oxygen demand (COD), TN and TP. MBFJNU-1 could grow well in undiluted swine slurry and artificial wastewater containing 30, 000 mg/L COD or 2000 mg/L TN. Furthermore, global nuclear DNA methylation (5-mC) of MBFJNU-1 was employed to explore the possible mechanism in response to wastewater stress. The results showed that the level of 5-mC was inversely proportional to the growth of MBFJNU-1 in different diluted swine slurry, helping to understand 5-mC variation in response to stress environment.